Respostas
respondido por:
3
a) (+3)+(+5)+(-2)+(1)+(+8)
3 + 5 - 2 + 1 + 8
8 +9 - 2
17 - 2
15
b) (-5)+(-6)+(-2)+(-5)
-5 - 6 -2 -5
-11 - 7
-18
3 + 5 - 2 + 1 + 8
8 +9 - 2
17 - 2
15
b) (-5)+(-6)+(-2)+(-5)
-5 - 6 -2 -5
-11 - 7
-18
respondido por:
0
a)
= (+3) + (+ 5) + (- 2) + (1) + (+8)
= 3 + 5 - 2 + 1 + 8
= 8 - 2 + 9
= 6 + 9
= 15
*******************************
b)
= (- 5) + (- 6) + (- 2) + (- 5)
= - 5 - 6 - 2 - 5
= - 11 - 7
= - 18
= (+3) + (+ 5) + (- 2) + (1) + (+8)
= 3 + 5 - 2 + 1 + 8
= 8 - 2 + 9
= 6 + 9
= 15
*******************************
b)
= (- 5) + (- 6) + (- 2) + (- 5)
= - 5 - 6 - 2 - 5
= - 11 - 7
= - 18
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás